The value of Gray scale, color doppler and ultrasound guided- FNA in detection metastasis to the axillary lymph node in patient with primary breast cancer. - Jabbar, Jinan A.; Fahad, Qusay A.; Al -Tememy, Enam A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Ultrasound guided fine needle aspiration (FNA) is a quick nonmorbid method of staging disease in the axilla,Color doppler ultrasound is used to differentiate benign lymph node from node that bears metastasis.Objective: To evaluate the utility of ultrasound guided (FNA) of the axillary L.N depending on the size of the primary tumor and the appearance of the lymph node by ultrasound , and to document the difference in color Doppler flow features between benign and malignant lymph node in women with primary breast cancer.Patients and methods: The total number of the patient in the study is (60). Data were collected about tumor size, lymph node appearance and color-power Doppler sonography compared to the result of ultrasound- guided FNA . Lymph node were classified as: Benign: if the cortex was even and measure < 3mm. Indeterminate : if the cortex was even but measure ≥ 3mm, or with focal cortical thickening but cortical thickness 2cm.The sensitivity and specificity of ultrasound guided FNA to detect metastasis to axillary lymph node was 67% for indeterminate lymph node, and 95% for suspicious lymph node. The sensitivity and specificity of ultrasound guided FNA to detect metastasis to axillary node in correlation to color Doppler flow was 100% for mixed vascularity and 100% for peripheral vascularity.Conclusion: There is a strong significant correlation relationship between the presence of peripheral blood flow in addition to the morphological changes which include focal cortical thickening >3mm and loss of hilum ,and the size of the primary tumor with presence of malignancy in LN in patient with primary breast cancer.